1991
DOI: 10.1002/eji.1830210350
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2‐dependent activation of tumor‐specific cytotoxic T lymphocytes in vivo

Abstract: We have quantitatively studied the effect of interleukin (IL) 2 on the cytotoxic T lymphocyte (CTL) response to tumor cells in vivo. Mastocytoma P815 was transfected with murine IL 2 cDNA (P815-IL 2) and injected into syngeneic mice. The anti-tumor response was analyzed and compared with the response induced by the non-transfected cells. P815 parental cells are highly tumorigenic, causing death within 20-30 days. In contrast, IL 2-transfected cells were totally rejected. Co-injection of IL 2-secreting and pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…When the IL-2, or IL-4-secreting cells were present in a 10-fold excess, initial delay in the growth of the unmodified cells was observed, but rapidly growing tumours eventually formed in all animals ( Figure 3). These data are in contrast to several previous studies, which have demonstrated effective induction of parental tumour rejection by admixture of 50% IL-2 Ley et al, 1991), or IL-4-secreting cells (Tepper et al, 1989;Golumbek et al, 1991).…”
Section: Methodscontrasting
confidence: 99%
See 4 more Smart Citations
“…When the IL-2, or IL-4-secreting cells were present in a 10-fold excess, initial delay in the growth of the unmodified cells was observed, but rapidly growing tumours eventually formed in all animals ( Figure 3). These data are in contrast to several previous studies, which have demonstrated effective induction of parental tumour rejection by admixture of 50% IL-2 Ley et al, 1991), or IL-4-secreting cells (Tepper et al, 1989;Golumbek et al, 1991).…”
Section: Methodscontrasting
confidence: 99%
“…However, another report describes a complete absence of induction of protection by IL-4-secreting plasmacytoma cells (Tepper et al, 1992). Two reports described lasting protection induced by IL-2-secreting cells Ley et al, 1991), the work of Ley et al (Ley et al, 1991) demonstrated an enhanced protection compared to parental mastocytoma cells. The study of Fearon et al described short-term protection induced by IL-2-secreting colon tumour cells which is greatly diminished after 28 days (Fearon et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations